Assessment of Tamoxifen-Related Endometrial Changes in Premenopausal Female Patients With Diffusion-Weighted Magnetic Resonance Imaging. Issue 4 (July 2020) - Abdel Razek, Ahmed Abdel Khalek; Elkalla, Hend M. Hamdey Rashed; Refky, Basel; Elsergany, Aliaa; Sakrana, Amal Abdelsattar; Saleh, Gehad; Gadelhak, Basma N.
Abstract : Purpose: To evaluate tamoxifen-related endometrial changes in premenopausal female patients with diffusion-weighted magnetic resonance imaging (DWI). Methods: This prospective study was performed on 71 premenopausal female patients (mean age, 41 years) who were receiving tamoxifen therapy. All patients underwent magnetic resonance imaging with DWI of the pelvis and hysteroscopic-guided endometrial biopsy. The apparent diffusion coefficient (ADC) values of the endometrial plate were calculated and correlated with pathological results. Results: The mean ADCs of tamoxifen-related benign endometrial lesions (1.35 ± 0.19 and 1.32 ± 0.13 × 10 −3 mm 2 /s) were significantly higher ( P = 0.001) than those of normal endometrial plate (0.95 ± 0.11 and 0.93 ± 0.11 × 10 −3 mm 2 /s) by both reviewers, respectively. The cutoff ADC values used to differentiate tamoxifen-related benign endometrial lesions from normal endometrium were 1.07 and 1.02 × 10 −3 mm 2 /s with areas under the curve of 0.94 and 0.93 and accuracy of 94.4 and 95.8 by both reviewers, respectively. The mean ADC values of endometrial polyp (EP) (1.44 ± 0.19 and 1.42 ± 0.22 × 10 −3 mm 2 /s) were significantly higher ( P = 0.001) than those of endometrial hyperplasia (EH) (1.25 ± 0.19 and 1.23 ± 0.19 × 10 −3 mm 2 /s) by both reviewers, respectively. The cutoff ADC values used to differentiate EP from EH were 1.38 × 10 −3 and 1.36 × 10 −3 mm 2 /s with areas under the curve of 0.81 and 0.77 and accuracy of 80% and 70% by both reviewers, respectively. There was an insignificant difference in ADC value between typical and atypical EH. The ADC values of endometrial cancer (0.80 and 0.78 × 10 −3 mm 2 /s) were lower than those of tamoxifen-related benign endometrial lesions. The final diagnosis was normal endometrium (n = 36), benign endometrial lesions either EH (n = 17), or EP (n = 16), and endometrial cancer in only 2 patients. Conclusions: We concluded that DWI helps in detection and characterization of different tamoxifen-related endometrial changes in the premenopausal female patients.